The networks of cities in Argentina (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2015)
The intermunicipality is understood as the institutionalized articulation of interconnected and interdependent local governments to collectively implement one or more policies under the principle of horizontal coordination. This research is diachronic-retrospective and qualitative-quantitative contemplated the analysis of 255 intermunicipal initiatives of all kinds in the last three decades of argentine history. This article analize some city national networks and the international networks in which argentine local governments participate. The results show the small number of initiatives and its temporary volatility, with a low impact on the public agenda; also the low participation of argentine governments in a small group of international city networks. We conclude that city networks are a mechanism unexplored in Argentina, which it will merit attention and intensive policies.
Keywords: intermunicipality; Argentina; local government; networks; cities